2023
DOI: 10.1007/s12633-023-02464-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of High Filler Loading of SiO2 on the Mechanical and Dynamic Mechanical Analysis of Natural PALF fibre-Based Hybrid Composite

Abstract: This work aims to investigate the effect of SiO 2 nanoparticles on the mechanical properties of pineapple leaf ber (PALF) epoxy hybrid composites. The compression molding process was used to create the composite. To achieve the aforementioned goals, the blends were made using 25% PALF and varied weight proportions (3wt%, 6wt%, and 9wt%) of SiO 2 nanoparticles. Tensile, bending, impact, interlaminar shear, shoreline D hardness, and dynamic mechanical analysis were all evaluated. SEM was used to examine the morp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…found that basalt fibre-reinforced polymeric bars had reduced glassy transitional rates caused by the plasticity impact. Additionally, the upward trajectory of the Tg values in the present investigation is consistent with those of previous studies that have been described in the literature [51,52]. On the other hand, figure 11 demonstrates that the storage modulus of the moist hybrids containing 3% and 4.5 wt% SiO 2 was greater compared to that of the dry specimens.…”
Section: Dynamic Mechanical Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…found that basalt fibre-reinforced polymeric bars had reduced glassy transitional rates caused by the plasticity impact. Additionally, the upward trajectory of the Tg values in the present investigation is consistent with those of previous studies that have been described in the literature [51,52]. On the other hand, figure 11 demonstrates that the storage modulus of the moist hybrids containing 3% and 4.5 wt% SiO 2 was greater compared to that of the dry specimens.…”
Section: Dynamic Mechanical Propertiessupporting
confidence: 92%
“…This weakens the connection among the SiO 2 nanoparticles and creates micropores that let water droplets pass among them. Minimal Van der Waals forces link to the additive agglomeration in the present situation [52]. As seen in the results obtained with the addition of 3 wt% and 4.5 wt% SiO 2 water soaking, that may lead to an impairment of the bonding capability of the hybrid materials and a considerable decrease in Tg levels.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 52%